Standing Up to the Gender Ideologues: a Quillette Editorial (Quillette, 2021)
On June 23rd, Britain’s Royal Academy of Arts put out a carefully worded five-paragraph media statement regarding German-born textile artist Jess de Wahls. “We have apologised to Jess de Wahls for …